2017
DOI: 10.1519/jsc.0000000000001555
|View full text |Cite
|
Sign up to set email alerts
|

Vertical- vs. Horizontal-Oriented Drop Jump Training: Chronic Effects on Explosive Performances of Elite Handball Players

Abstract: Dello Iacono, A, Martone, D, Milic, M, and Padulo, J. Vertical- vs. horizontal-oriented drop jump training: chronic effects on explosive performances of elite handball players. J Strength Cond Res 31(4): 921-931, 2017-This study aimed to assess the chronic effects of vertical drop jump (VDJ)- and horizontal drop jump (HDJ)-based protocols on neuromuscular explosive abilities, such as jumping, sprinting, and changes of direction (COD). Eighteen elite male handball players (age 23.4 ± 4.6 years, height 192.5 ± 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
52
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 41 publications
1
52
0
1
Order By: Relevance
“…this superior gain on 40-m shuttlesprint speed might be attributed to specific adaptations on muscle mechanical properties, as a result of the higher time spent accelerating per running bout in the SrIt-3 model, which also implies in longer periods of time applying horizontal forces. Dello Iacono et al [45] also found that horizontal-drop jump training resulted in larger gains in short-sprint (i.e., 10-m) and change of direction capabilities in comparison with the vertical-drop jump group. Additionally, Mc-Kenzie et al [48] showed that horizontal jump performance significantly improved after individualized optimal handheld loading in comparison with unloaded jumps (i.e., control) in female netball players.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…this superior gain on 40-m shuttlesprint speed might be attributed to specific adaptations on muscle mechanical properties, as a result of the higher time spent accelerating per running bout in the SrIt-3 model, which also implies in longer periods of time applying horizontal forces. Dello Iacono et al [45] also found that horizontal-drop jump training resulted in larger gains in short-sprint (i.e., 10-m) and change of direction capabilities in comparison with the vertical-drop jump group. Additionally, Mc-Kenzie et al [48] showed that horizontal jump performance significantly improved after individualized optimal handheld loading in comparison with unloaded jumps (i.e., control) in female netball players.…”
Section: Discussionmentioning
confidence: 94%
“…this manipulation will impact on the number of times that players should apply force horizontally into the ground to overcome the inertia and move their bodies forward as rapidly as possible throughout a given workout. recent studies have shown that the development of training strategies (e.g., horizontally-directed exercises) which prioritize the application of force in the horizontal direction are paramount to significantly improve sprinting speed [45][46][47]. the present study found that the 40-m shuttle-sprint speed was very likely (99% chances of a real effect) improved after SrIt-3, but unclear changes (64/28/08%; ES = 0.33) were noticed following the SrIt-1 training model.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of the present study revealed that the plyometric interventions used were inadequate to produce significant improvements in COD ability of highly trained athletes despite the improvements in short distance sprint performance for the H-L group, indicating that an alternative stimulus may be required for COD enhancement. It has been suggested that the effectiveness of plyometric training for improving COD ability may be dependent on the manner in which they are performed, with regards to force-vector specificity [41,42,43,44,45,46]. Differences between plyometric training performed unilaterally compared to bilaterally have also been observed [19,47].…”
Section: Discussionmentioning
confidence: 99%
“…Some investigations into force-vector specificity and comparisons of unilateral and bilateral exercises within eccentric overload training have also been conducted, with unilateral multidirectional exercises producing more robust adaptations in COD performance, and bilateral vertical exercises displaying more robust adaptations in vertical jump, and sometimes linear sprint, performance [19,47]. Dello Iacono and colleagues [41] compared the effects of vertical and horizontal single-leg drop jump training in elite handball players and found stark differences in favor of the horizontal drop jump training group with regards to sprint and COD performance. It is therefore possible given the highly trained nature of the subjects that drop jumps performed in the present study may have been more suitable for enhancements in COD ability if they were performed in a unilateral multidirectional, rather than bilateral vertical, manner.…”
Section: Discussionmentioning
confidence: 99%
“…Seam bowlers are exposed to up to 9 times body mass during the delivery phase of seam bowling28 . This exposure can be over 300 times during a game, which over time is a considerable training stimulus, given previous research has shown as little as 120 high load drop jumps per week for 10 weeks has enhanced 10m sprint times29 . As minimal sprinting kinematic differences have been demonstrated in fielding positions30 , it is logical to suggest that the moderate differences in sprinting profiles are not fielding related.…”
mentioning
confidence: 99%